The Role of Price, Taste, and Brand Image in Purchasing Decisions - Yahya, Moch Roziqi; Ambarwati, Rita (Almana : Jurnal Manajemen dan Bisnis, 2024)
Each company innovates its product as a result of developing food varieties that produce similar goods. This study aims to determine the effect of price, taste, and brand image on purchasing decisions for Mie Sedaap Ayam Bakar Limau located in Sidokerto Village, Sidoarjo Regency. This exploration uses quantitative techniques. information collection technique using a Simple Random Sampling Technique. the sample in this study amounted to 100 respondents. Collecting data used in this study using a questionnaire with a Likert scale. The data analysis used is the classical assumption test and multiple linear regression analysis. Hypothesis testing uses the F, t, and R2 tests. The results of this study indicate that simultaneously price, taste, and brand image have a positive and significant effect on purchasing decisions. Fcount is 160.249 > Ftable 2.699 and a significance value of 0.000b <0.05. Partially the price is a very positive and significant effect. Taste has a positive and significant effect. Brand image has a positive and significant effect on purchasing decisions for Mie Sedaap Ayam Bakar Limau.